Analysis Of Models In Development In Information Systems - Aswati, Safrian; Mulyani, Neni; Amin, Muhammad; Firmansyah, Ada Udi; *, Suhendra (IJRDO -Journal of Computer Science Engineering, 2017)
Development of information technology now requires organizations, companies or other institutions to follow these developments. One manifestation of the development of information technology is with the existing software that can simplify the data processing jobs. The software is in the form of information systems. Information systems can replace existing systems in the organization in terms of data processing. When the system will be developed into an information system required models in its development. These system development models provide detailed steps to produce a quality information system. There are many models used in system development such as Waterfall, Spiral, Rapid Application Development (RAD), The Open Group Architecture Framework (TOGAF), Zachman and COBIT. Each of these models provides different stages in system development. The main pillar of this model is the System Development Life Cycle (SDLC) which can be assumed as a classical methodology in system development. In this study the authors analyze some of the models used in system development Later this model can be used as a reference of a system analyst when will develop the system.